2016
DOI: 10.2139/ssrn.2845797
|View full text |Cite
|
Sign up to set email alerts
|

Location Choices of Chinese Multinationals in Europe: The Role of Overseas Communities

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 96 publications
(114 reference statements)
0
29
0
Order By: Relevance
“…Several studies point at the special role of highly skilled migrants, relative to low skilled ones, when it comes to orienting FDIs towards their countries of origin (Javorcik et al, 2011;Leblang, 2010). Others find evidence for FDIs going from the migrants' countries of origin to specific locations in the countries of destination, in particular those hosting the largest migrant communities (Hernandez, 2014;Karreman, Burger, & van Oort, 2017;Shukla & Cantwell, 2018).…”
Section: Migrant Inventors: Cross-border Network and International Ementioning
confidence: 99%
“…Several studies point at the special role of highly skilled migrants, relative to low skilled ones, when it comes to orienting FDIs towards their countries of origin (Javorcik et al, 2011;Leblang, 2010). Others find evidence for FDIs going from the migrants' countries of origin to specific locations in the countries of destination, in particular those hosting the largest migrant communities (Hernandez, 2014;Karreman, Burger, & van Oort, 2017;Shukla & Cantwell, 2018).…”
Section: Migrant Inventors: Cross-border Network and International Ementioning
confidence: 99%
“…In this direction, other studies can be cited. Karreman, Burger and Oort (2016) used fDi Markets (2003-2010, from the Financial Times, and the European Investment Monitor (2003Monitor ( -2009, from EY consultancy, as data sources to analyse the location choices of Chinese multinationals in Europe. Both sources contain information on greenfield investment projects announced in the media by companies, financial information providers, etc.…”
Section: Multinational Companies From Developing Countries Investing mentioning
confidence: 99%
“…Developing countries were initially the preferred recipients of foreign investments, even though Chinese state-owned enterprises have acquired shares of companies in developed countries, such as the USA and European Union countries (Karreman, Burger and Oort 2016). Since 2010, foreign direct investment (FDI) by Chinese companies in South American countries has increased considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research within relational economic geography, however, has demonstrated that factors within host countries such as the presence of overseas Chinese communities are also important in facilitating OFDI. Ethnicity‐based networks act as nodes of knowledge and information exchange, assisting Chinese MNCs to reduce communication barriers and obtain local knowledge (Deng et al., 2020; Hamzah, 2020; Karreman et al., 2017; Liang et al., 2019). Their presence, especially in new overseas markets, may be particularly important to helping PEs and smaller SOEs gain footholds.…”
Section: Introductionmentioning
confidence: 99%